PROFIL PENERAPAN MANAJEMEN BERBASIS SEKOLAH DALAM MEWUJUDKAN MUTU PENDIDIKAN SEKOLAH DASAR ISLAM TERPADU DI KECAMATAN NONGSA KOTA BATAM - Hadi, Moh. Badaruddin; Tatminingsih, Sri; Dahlan, Jarnawi Afghani (Jurnal Dedikasi Pendidikan, 2022)
The purpose of this study is to describe the description of the application of school-based management in Integrated Islamic Elementary Schools in Nongsa District, Batam City and the quality of education of Integrated Islamic Elementary Schools in Nongsa District, Batam City. conducted in SDIT which is located in Nongsa sub-district, Batam City. The participants/informants of this research are; 1) Principal; 2) Teacher; 3) Employees 4) School Committee at Integrated Islamic Elementary School in Nongsa District, Batam City. Data collection through interviews, observation, and documentation. Data analysis includes data collection, data selection, data display, conclusion drawing and verification. School-based management at the Integrated Islamic Elementary School in Nongsa District, Batam City is quite optimal. SBM is implemented by implementing a school-based learning curriculum that refers to the Education Office and is combined with an integrated learning model that is typical of Islamic schools, school-based student management, school-based management of educators and education personnel, sapras management, school-based financing management, school relations management and education. school-based society. school-based cultural and environmental management, while the education quality of the Integrated Islamic Elementary School in Nongsa District, Batam City is adequate both in academic and non-academic aspects.